INCIDENCE OF CONTAGIOUS ECTHYMA (ORF) IN GOATS IN AN ORGANIZED FARM - N. Bharathy; N. Akila (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An observation on the incidence of contagious ecthyma in goats was made at Mecheri Sheep Research Station, Pottaneri, Salem, Tamil Nadu, India, during summer season. Out of 154 goats maintained 20 of them had lesions suggestive of Contagious ecthema (orf). The affected animals were dull and depressed and had pyrexia. The external skin lesions were observed on the muzzle, nostrils and lips. The morbidity percentage was 13% and there was no mortality. Samples were collected from 30% of the affected animals (Dried scab in 50 % glycerol saline) and samples sent to Central University laboratory for confirmative diagnosis and out of six samples tested for orf, five scab samples were found positive by the polymerase Chain reaction. Affected animals were kept in isolation and treated with intravenous fluid like dextrose normal saline for restoring ionic balance, antibiotic (Streptopencillin) to prevent secondary bacterial infection, anti-inflammatory drugs (Meloxicam) and antihistamines (Pheniramine maleate). The B complex, vitamins and ragi gruel were drenched to the affected animals as supportive therapy, as they were anorectic due to painful oral lesions. Lesions were cleaned with Potassium Permanganate solution (1:1000). Ayurvedic treatment like Neem oil and Turmeric paste or glycerin and boric acid paste were applied on external lesions. Animals were completely recovered after two weeks of continuous treatment.